Presence of TRPA1 Modifies CD4+/CD8+ T Lymphocyte Ratio and Activation - Katalin Szabó; Ágnes Kemény; Noémi Balázs; Esam Khanfar; Zoltán Sándor; Ferenc Boldizsár; Rolland Gyulai; József Najbauer; Erika Pintér; Tímea Berki (MDPI AG, 2022)
Transient Receptor Potential Ankyrin 1 (TRPA1) has been reported to influence neuroinflammation and lymphocyte function. We analysed the immune phenotype and activation characteristics of TRPA1-deficient mice (knockout-KO) generated by targeted deletion of the pore-loop domain of the ion channel. We compared TRPA1 mRNA and protein expression in monocyte and lymphocyte subpopulations isolated from primary and secondary lymphatic organs of wild type (WT) and KO mice. qRT-PCR and flow cytometric studies indicated a higher level of TRPA1 in monocytes than in lymphocytes, but both were orders of magnitude lower than in sensory neurons. We found lower CD4+/CD8+ thymocyte ratios, diminished CD4/CD8 rates, and B cell numbers in the KO mice. Early activation marker CD69 was lower in CD4+ T cells of KO, while the level of CD8+/CD25+ cells was higher. In vitro TcR-mediated activation did not result in significant differences in CD69 level between WT and KO splenocytes, but lower cytokine (IL-1β, IL-6, TNF-α, IL-17A, IL-22, and RANTES) secretion was observed in KO splenocytes. Basal intracellular Ca2+ level and TcR-induced Ca2+ signal in T lymphocytes did not differ significantly, but interestingly, imiquimod-induced Ca2+ level in KO thymocytes was higher. Our results support the role of TRPA1 in the regulation of activation, cytokine production, and T and B lymphocytes composition in mice.